The face of mammon the matter of money in English Renaissance literature - Landreth, David, 1973- (Oxford : Oxford University Press, 2012)
'The Face of Mammon' studies the coins of 16th-century England as they are articulated in literary writing. It argues that the coinage of the 16th century is a very different object from the money that we know in that modern money is the object of a discourse, economics, that had not yet taken shape.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Money in literature; Coinage in literature; Wealth in literature; Material culture in literature; Money -- Great Britain -- History -- 16th century; Money -- Great Britain -- History -- 17th century